An efficient approach for recyclable waste detection and classification using image processing techniques - Chowdhury, Prabal Kumar; Islam, Md. Aminul; Haque, Md Aminul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.